Density‐weighted concentric rings k‐space trajectory for 1H magnetic resonance spectroscopic imaging at 7 T. (18th October 2017) - Chiew, Mark; Jiang, Wenwen; Burns, Brian; Larson, Peder; Steel, Adam; Jezzard, Peter; Albert Thomas, M.; Emir, Uzay E.
Abstract : It has been shown that density‐weighted (DW) k ‐space sampling with spiral and conventional phase encoding trajectories reduces spatial side lobes in magnetic resonance spectroscopic imaging (MRSI). In this study, we propose a new concentric ring trajectory (CRT) for DW‐MRSI that samples k ‐space with a density that is proportional to a spatial, isotropic Hanning window. The properties of two different DW‐CRTs were compared against a radially equidistant (RE) CRT and an echo‐planar spectroscopic imaging (EPSI) trajectory in simulations, phantoms and in vivo experiments. These experiments, conducted at 7 T with a fixed nominal voxel size and matched acquisition times, revealed that the two DW‐CRT designs improved the shape of the spatial response function by suppressing side lobes, also resulting in improved signal‐to‐noise ratio (SNR). High‐quality spectra were acquired for all trajectories from a specific region of interest in the motor cortex with an in‐plane resolution of 7.5 × 7.5 mm 2 in 8 min 3 s. Due to hardware limitations, high‐spatial‐resolution spectra with an in‐plane resolution of 5 × 5 mm 2 and an acquisition time of 12 min 48 s were acquired only for the RE and one of the DW‐CRT trajectories and not for EPSI. For all phantom and in vivo experiments, DW‐CRTs resulted in the highest SNR. The achieved in vivo spectral quality of the DW‐CRT method allowed for reliable metabolic mapping of eight metabolites including N‐acetylaspartylglutamate, γ‐aminobutyric acid and glutathione with Cramér‐Rao lower bounds below 50%, using an LCModel analysis. Finally, high‐quality metabolic mapping of a whole brain slice using DW‐CRT was achieved with a high in‐plane resolution of 5 × 5 mm 2 in a healthy subject. These findings demonstrate that our DW‐CRT MRSI technique can perform robustly on MRI systems and within a clinically feasible acquisition time. Abstract : In this study, we developed a density weighted (DW) MRSI acquisition technique at 7T that addresses the challenges of speed, spatial resolution and side lobe artifacts. For this, we proposed to use concentric rings k‐space trajectory (CRT) to sample k‐space with a density proportional to an isotopic, spatial Hanning window. We also demonstrated the implementation of this novel DW‐CRT at 7T through a quantitative comparison with radially equidistant (RE) CRT and EPSI acquisitions in simulations, phantoms and in vivo experiments. The data of the proposed DW‐CRT MRSI showed significantly reduced side lobes together with an increased SNR. The high‐quality metabolic mapping using DW‐CRT was achieved with a high in‐plane resolution of 5x5 mm